Agile Governance In Handling the Covid-19 Pandemic by The Kampar District Health Office in 2021 - Suci Ramadyah; Hasim As'ari; Nur Laila Melani (Department of Public Administration, 2022)
The concept of agile governance or called government that is agile, agile or fast has started to be discussed recently. Agile Governance increasingly has a strategic value in the midst of the condition of the Indonesian state which has been hit by the Covid-19 pandemic since 2020. The highest spike in Covid-19 cases in Kampar Regency occurred in August 2021 since the establishment of Covid-19 as a pandemic on March 31 2020. The purpose of this research is to find out how Agile Governance is implemented in efforts to deal with the Covid-19 pandemic carried out by the Health Service Kampar Regency. This study uses a qualitative research method with an explanatory approach. Researchers conducted data analysis based on the Agile Governance concept of Shah and Stephens’s theory. The research was conducted at the Kampar District Health Office in 2021. The results of this study indicate that the Health Office has implemented Agile Governance in an effort to deal with the Covid-19 pandemic in accordance with the applicable technical guidelines and standard operating procedures, but public distrust of Covid-19 has become obstacles for the Health Office in handling and providing services to the community in the Kampar Regency area.